2019
DOI: 10.1097/bsd.0000000000000850
|View full text |Cite
|
Sign up to set email alerts
|

Contained-Delivery Route and the Administration of Postoperative Steroids Following Anterior Cervical Spinal Fusion With Low-dose rhBMP-2 Reduces the Magnitude of Respiratory Compromise

Abstract: Study Design: Retrospective chart review of patients who underwent anterior cervical discectomy and fusion (ACDF) using low-dose recombinant human bone morphogenic protein (rhBMP)-2. Objective: Determine whether severity and incidence of respiratory complications after ACDF surgery are decreased when using a low-dose BMP-infused sponge within a constrained carrier and postoperative IV and oral steroids. Summary of Backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…In our study we did not present a control group for comparison, but our rate of cervical swelling appeared to fall within the control group range of 0.0-13.9% in the aforementioned studies. Interestingly, Maza et al 30 showed that using a contained delivery device for rhBMP-2 significantly reduced postoperative swelling complications. For ACDF, J.P.M.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we did not present a control group for comparison, but our rate of cervical swelling appeared to fall within the control group range of 0.0-13.9% in the aforementioned studies. Interestingly, Maza et al 30 showed that using a contained delivery device for rhBMP-2 significantly reduced postoperative swelling complications. For ACDF, J.P.M.…”
Section: Discussionmentioning
confidence: 99%
“…Although BMP is one of the most popular growth factors which are known as triggering / signaling molecules that regulate not only growth but also repair and regeneration [1,21] by promoting osteogenesis, chondrogenesis, vascularization and formation of fibrotic tissue to accelerate the maturation progress and callus formation while inhibiting osteoclastogenesis [8], decreasing blood loss, surgery time and hospital stay [20,21]; the use of BMPs is still avoided by many physicians because of their complications such as an increase incidence in dysphagia, significant prevertebral swelling, airway edema compromise [1,2,20,51], uncertain impacts in promoting tumorigenesis and tumor metastasis [45,52], ectopic bone formation, osteophyte production [1,20,43,44]. It is also reported that BMP-2 induces PPARγ activation in a dose dependent manner and promotes the commitment of MSCs to adipocyte lineage [20,53].…”
Section: Bmp9 Bmp10mentioning
confidence: 99%
“…There are also various applications of BMPs and TGFβs in clinics with carrier molecules [51,[75][76][77][78][79][80][81][82][83][84]. However, the locally applied supraphysiological BMP-2 doses during surgery is reported to be connected with hematoma formation in soft tissue, increased inflammatory response, bone cysts and infection [85] which also increase the importance of clinical follow-up studies.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent literature has demonstrated some evidence of safety in usage of lower rhBMP-2 doses and especially when these were delivered in contained devices. 1,11 Tumialán et al reviewed 200 patients who underwent a single-or multilevel ACDF with PEEK spacers filled with a collagen sponge impregnated with low-dose rhBMP-2. 1 In their report, the authors concluded that the incidence of symptomatic dysphagia may be reduced with lower doses of rhBMP-2 that are placed only within the PEEK spacer.…”
mentioning
confidence: 99%